As Unidades de Apoio Pedagógico e os contextos emergentes: processos formativos na universidade - Pappis, Lisiane (2020)
This work is part of the Research Line - LP1 Training, Knowledge and Professional Development, through the Postgraduate Program in Education (PPGE) in the Master's course in Education at Universidade Federal de Santa Maria (UFSM). This research presents as a theme the work developed in the Pedagogical Support Units of a public higher education institution and the emerging contexts. The PSUs represent minimum structures of the University Centers of the institution and have the intention to develop and to assist activities that involve management, professors, students and administrative workers. In this sense, this study aims to understand which propositions are promoted by the Pedagogical Support Units to meet the emerging contexts and their repercussions in the training processes. It is necessary to notice that emerging contexts are understood as the changes and transformations that occur in the area of Education that involve the social, cultural, political and global spheres which impact on new ways of knowledge and teaching. In this perspective, the adopted methodology will be of a qualitative nature with a socio-cultural narrative approach based on the studies of Bolzan (2002,2009), which was based on the studies of Vygotski (2007), Bakhtin (2006, 2010), Freitas (2010), Clandinin and Connelly (2015). As research instruments, narrative interviews are presented, with guidance topics and an exploratory study about the PSUs, aiming to realize a reading with regards to overall context as well as to the workers subject of the study. Selected employees were the coordinators of the PSUs. A problematization of such thematic is based upon the studies of Marcelo (2009), Freire (1996), Marcelo e Vaillant (2018), Tardif (2014), Isaia and Bolzan (2005, 2006, 2007), Bolzan (2009, 2016), Cunha (2014, 2015, 2016), Lucarelli (2019), among others whose efforts point towards higher education degrees (undergraduated und graduated). With this work, we show that the training processes are the guiding axis of the activities of the PSUs and that they are linked to the institutional dynamics and to the emerging contexts as elements that impact the ways of teaching practices of these Units. These elements reflect on challenges and confrontations permeated by the academic culture instituted and experienced in teaching centers. Moreover, a drawing of the PSUs and its pedagogic management are presented based upon the narratives and on the intitutional dynamics. Therewith it was possible to recognize the organization as well as how the coordinators perform their activities, being faced by constant challenges from admnistratove and finantial origin, or even from an intitutional and academic culture. Furthermore, it was verified that the emerging contexts present elements that impact on the work of those units and, consequently, on the formative process promoted from themselves. In this way, as delimiters for the emerging contexts, the PSUs coordinators are point the macro and micro policies besides the generation of the worker depending on the existent intergeneration present in the University. They consider the new student profile not only as a characterization element of the emerging contexts, but also as a confrontation to their own actions and especially to those of the professors. In face of those facts, we observed that the sensible hearing is the work strategy that prevail among PSUs coordinators as a mean to approximate and to give voice to students, professors and administrative workers. Such hearing aims to enable the democratization of the speech, consequently enabling both conversations and actions focused on the needs of the subjects. Therefore, the PSUs have the significant role for the formative processes of teaching and learning in the academic environment, enabling time and place for reflection that might sensitize the academic community as a whole to face the challenges that emerge within the institution.